Communities’ perceptions and knowledge of ecosystem services: Evidence from rural communities in Nigeria - Zhang, Wei; Kato, Edward; Bhandary, Prapti; Nkonya, Ephraim M.; Ibrahim, Hassan Ishaq; Agbonlahor, Mure Uhunamure; Ibrahim, Hussaini Yusuf (International Food Policy Research Institute, 2015)
This research has been undertaken to improve our understanding of stakeholders’ knowledge and perception about ecosystem services (ES), which provides a valuable means of gaining insight into the opportunities and constraints that face ES management in a multiuser landscape. Land use preferences are influenced by a variety of motives, attitudes, and values intrinsic to every individual’s decisionmaking. Knowledge can affect attitudes and behavioral intentions, and a positive attitude toward the environment has been found to predict conservation practices.